Effect of Driving Signals on Motion Characteristics of Multilayer Electrostatic Actuator Supported by Only Lubricating Liquid - Md Ghazaly, Mariam (Elsevier, 2012)
The present paper describes the characteristic switching of a multilayer thin electrostatic actuator supported by only lubricating oil and its application in the control of an ultra-precision fine stage.